2010
DOI: 10.1063/1.3502105
|View full text |Cite
|
Sign up to set email alerts
|

Diminished cage effect in solid p-H2: Infrared absorption of CH3S observed from photolysis in situ of CH3SH, CH3SCH3, or CH3SSCH3 isolated in p-H2 matrices

Abstract: We report the infrared absorption spectrum of the methylthio (or thiomethoxy) radical, CH(3)S (X  (2)E(3/2)), produced via photodissociation in situ of three precursors CH(3)SH, CH(3)SCH(3), and CH(3)SSCH(3) isolated in solid p-H(2). The common absorption features observed with similar intensity ratios in each experiment are assigned to CH(3)S. The wavenumbers of these features agree satisfactorily with those predicted with a spin-vibronic Hamiltonian accounting for the anharmonic effects and the Jahn-Teller e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 79 publications
1
24
1
Order By: Relevance
“…The three absorption peaks at 2817, 2911, and 2978 cm À1 are attributed to the stretching modes of the ÀCH 3 group in the [Cu(SCH 3 )] 1 nanowires. [7] The peak at 1414 cm À1 is due to antisymmetric methyl deformation, [8] and the strong peak at 934 cm À1 is from the H-C-S bending. [9] The stretching frequency for the CÀS bond was observed at 681 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The three absorption peaks at 2817, 2911, and 2978 cm À1 are attributed to the stretching modes of the ÀCH 3 group in the [Cu(SCH 3 )] 1 nanowires. [7] The peak at 1414 cm À1 is due to antisymmetric methyl deformation, [8] and the strong peak at 934 cm À1 is from the H-C-S bending. [9] The stretching frequency for the CÀS bond was observed at 681 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…They are consistent with values of ν 3 , 2ν 4 , and ν 4 modes of CH 3 in p-H 2 reported previously. 31,34 After irradiation at 254 nm for 6.5 h, weak lines of CH 4 at 3026.0/3025.2 and 1308.3/1308.2 cm −1 appear. Annealing of the matrix at 4.7 K for 2 min after the irradiation showed intense lines due to C 2 H 6 , indicating that CH 3 is produced upon photolysis and might diffuse in solid p-H 2 at 4.7 K. Momose et al also observed CH 4 and C 2 H 6 upon irradiation of CH 3 I at 184.9 nm for 2.5 h in a p-H 2 matrix.…”
Section: B Photolysis Of Ch 3 I/so 2 /P-h 2 Matricesmentioning
confidence: 99%
“…The quantum solid para-hydrogen (p-H 2 ) has a diminished cage effect that allows the production of free radicals via photofragmentation [23][24][25] in situ or bimolecular reactions induced on irradiation. [26][27][28][29][30] In this work, we have photolyzed a CH 2 CHC(O)Cl/p-H 2 matrix at 3.2 K with laser light at 193 nm and observed absorption lines ascribable to 11 fundamental vibrational modes of 3-propenonyl (·CH 2 CHCO) radical.…”
Section: Introductionmentioning
confidence: 99%